2021
DOI: 10.1183/16000617.0374-2020
|View full text |Cite
|
Sign up to set email alerts
|

Waterpipe smoking: a review of pulmonary and health effects

Abstract: Waterpipe smoking is an old form of tobacco smoking, originating in Persia and the Middle East. The popularity of the waterpipe is increasing worldwide, particularly among young adults, and there are widespread misconceptions regarding its negative health effects. The inhaled smoke of the waterpipe contain several toxic and hazardous materials including nicotine, tar, polyaromatic hydrocarbons and heavy metals, all of which are proven to be related to lung diseases and cancer. Regular waterpipe smoking is asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 60 publications
0
21
0
2
Order By: Relevance
“…A systematic review and meta-analysis found that waterpipe smoking was associated with a heightened odds of certain types of cancer ( 11 ). Another review suggested that regular waterpipe smoking was positively associated with respiratory symptoms, lung disease, and reduced pulmonary function ( 12 ). Münzel et al also found that waterpipe and other tobacco product (tobacco cigarettes and e-cigarettes) use might increase the burden of symptoms in patients with coronavirus disease 2019 and cause more serious health consequences ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis found that waterpipe smoking was associated with a heightened odds of certain types of cancer ( 11 ). Another review suggested that regular waterpipe smoking was positively associated with respiratory symptoms, lung disease, and reduced pulmonary function ( 12 ). Münzel et al also found that waterpipe and other tobacco product (tobacco cigarettes and e-cigarettes) use might increase the burden of symptoms in patients with coronavirus disease 2019 and cause more serious health consequences ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Its short-term health issues may include headache, nausea, and dizziness, among others1. Long-term health effects include respiratory and pulmonary diseases as well as cardiovascular complications [45][46][47] . As seen in our findings, cough was the third most prevalent health symptom among males and older age categories specifically 35-44 years and 45-54 years.…”
Section: Discussionmentioning
confidence: 99%
“…Increased incidence of tobacco smoking was associated with psychophysical and behavioral factors [ 35 ]. WP smoking is being used increasingly amongst young adults in the Middle East [ 36 ]. This increase could be explained by the enhanced commercial sector of WP devices, accessories, and Muassel in Egypt and Syria.…”
Section: Discussionmentioning
confidence: 99%